Resilience and Coping Strategies of Junior High School Students in Dumaguete City - Eumague, Ma. Hezel B.; Rafols, Jaruvic C. (Silliman Journal, 2025)
At the beginning of distance learning, there was a notable surge in referrals to the guidance office due to behavioral changes among junior high school students. Consequently, this study aims to explore the crucial association between the level of resilience and coping strategies among Junior High School students in Holy Cross High School Dumaguete. Despite considerable research on resilience and coping methods, there is a limited body of knowledge concerning Filipino Junior High School students. The survey included 253 students who responded to two standardized questionnaires. Based on the findings, it was observed that the respondents exhibited a high level of resilience. This is a positive attribute on the part of the respondents since it brings to light that they believe they can achieve their goals despite obstacles. They can return quickly to normal condition after a difficult situation or event. This manifests their high adaptability to changes that are inevitable in human existence. Additionally, their coping strategies leaned more towards an approach-oriented approach rather than avoidant coping strategies. When confronted with an unpleasant situation, they devise and execute strategies to alleviate the existing condition. They also think of it as part of the reality in life. Lastly, the study revealed a significant relationship between the level of resilience and coping strategies among the respondents.